Cyanobacteria Community Dynamics and Trophic Status of Intensive Shrimp (Litopenaeus vannamei) Farming Pond in Situbondo East Java Indonesia - Dian Aliviyanti; Suharjono Suharjono; Catur Retnaningdyah (Journal of Tropical Life Science, 2017)
The objective of this study was to analyze the dynamics community structure of Cyanobacteria and trophic status in ponds of intensive shrimp culture (Litopenaeus vannamei) in Situbondo based on Trophic Diatom Index (TDI).  The ex post facto research was conducted in situ in the hamlet of Pond Mutiara Mas III Klatakan Situbondo East Java Indonesia.  Observation of Cyanobacteria and Diatoms community structure were done every week during four cycles of shrimp farming ponds.  Cycle of shrimp farming ponds is the times for enlargement process of the shrimps from seed to mature which ranges from 90-120 days.  The dependent variables were the density of Cyanobacteria and Diatoms community, as well as chemical parameters nitrite and orthophosphate.  Trophic status was determined from TDI be counted from data of diatom density.  All of the data were then classified using cluster and biplot analysis program PAST Ver. 3.11 to discribe the profile of ecosystem quality.  The research results showed that there were four taxa of Cyanobacteria during farming cycle which the highest density was found from the genus of Oscillatoria.  Based on the value of TDI, we found that the trophic status of water in shrimps pond during the production process was eutrophic until hyper-eutrophic.  The water quality was decreases along with the length of incubation time.